Optimization of Steamed Cake Quality Through the Use of Beet Flour: A Sensory Analysis - Nugroho, Setyo Prasiyono (Gastronary, 2024)
This study aims to evaluate the effect of beet flour concentration on the sensory quality of steamed sponge cake, including texture, moisture retention, taste, aroma, visual appearance, and consumer satisfaction levels. Based on interviews and Focus Group Discussions (FGD), it was found that using beet flour at concentrations of 10% and 20% resulted in steamed cakes with a soft texture and fine pores similar to standard steamed sponge cakes, while maintaining good moisture retention. At higher concentrations (30% and above), the cake texture became denser, slightly dry, and crumbly, and the beet flavor began to dominate, producing a strong earthy aftertaste that was not preferred by all consumers. The visual appearance also varied, with cakes containing 10-20% beet flour exhibiting an attractive and consistent pink to red color, while at concentrations of 30% or more, the color became too dark and uneven. Panelists with traditional preferences favored beet flour concentrations below 20% as they aligned more with the classic taste and texture of steamed sponge cake. In contrast, panelists seeking innovation and health benefits were more open to 20-30% concentrations, although they acknowledged the need to balance the dominant beet flavor. The highest satisfaction level was found in steamed cakes with 20% beet flour, as it provided an ideal balance between flavor innovation and maintained sensory quality. This study concludes that the use of beet flour up to 20% is widely acceptable and adds value to steamed sponge cakes in terms of taste, nutrition, and aesthetics.